Sustainable economic diversification in the Mangystau region: Strategic pathways and prospects - Taskarayeva, Maira; Alshanov, Rakhman; Dzholdasbayeva, Gulsara; Kirbasova, Leila; Kizimbayeva, Azhar (International Journal of Innovative Research and Scientific Studies, 2025)
Economic diversification is one of the key factors for the sustainable development of regions, especially those that are heavily dependent on the export of raw materials. International experience shows that countries that have successfully implemented diversification strategies, such as Australia and Norway, have not only reduced vulnerability to fluctuations in commodity markets, but have also developed sustainable economic models focused on innovation and human capital development. The purpose of this study is a comprehensive analysis of the economic situation in the Mangystau region in order to identify key problems and opportunities to reduce dependence on the oil and gas sector. Particular attention is paid to adapting the experience of Australia and Norway, which have successfully implemented diversification strategies that have ensured their economic sustainability. The study uses an integrated methodology that includes quantitative and qualitative methods of analysis, as well as a comparative analysis of the economic models of these countries, which allows us to identify the most relevant approaches for adaptation in regional conditions. The empirical base of the study is based on data from a structured survey involving 150 respondents from various social and professional groups, including representatives of business, government agencies, agricultural and tourism sectors. As a result of the analysis, priority areas of diversification were identified – tourism, agro-industrial complex and renewable energy. Norway's effective use of sovereign wealth funds and Australia's infrastructure reforms underscore the importance of strategic investments in sustainable development. To ensure successful diversification, measures have been proposed, including the creation of specialized industrial zones, improvement of the investment climate, and development of public-private partnership mechanisms. Long-term investments in renewable energy and the introduction of modern agricultural technologies can significantly reduce the region's dependence on the hydrocarbon sector, contributing to the creation of new jobs and an increase in household incomes. The implementation of educational initiatives aimed at training specialists for developing industries will increase the competitiveness of the region in modern economic conditions. The modernization of the transport and logistics infrastructure, including the expansion of port facilities and railway networks, will strengthen the region's trade ties, attracting foreign investment and expanding export potential. In addition, the development of ecotourism based on the natural and cultural heritage of the region will contribute not only to economic growth, but also to the social integration of the local population into sustainable development processes.